Implementasi Form Pendokumentasian SBAR terhadap Komunikasi Perawat saat Serah Terima Pasien - Yusnaini Yusnaini; Mariza Elvira; Dini Qurrata Ayuni; Sontina Saragih (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the implementation of the SBAR documentation form on nurse communication during patient handover. The method used is quasi-experimental, using a research design in the form of pre and post-test without control. The results showed an effect of implementing the SBAR documentation form on nurse communication during patient handover in the Bunda Thamrin General Hospital Medan inpatient room with an Asymp—Sig (2-tailed) value of 0.015. In conclusion, there has been an increase in SBAR-based nurse communication after implementing the SBAR documentation form. Therefore, it is recommended that hospital management be able to stimulate and provide rewards for nurses dedicated to realizing SBAR documentation and communication during patient handover. Keywords: Communication, Documentation, SBAR, Patient Handover